Analisis Konten pada Buku Interaktif Pop-up Harry Potter - Asy Syifa Tsaniya Adha; Aditya Januarsa (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Pop-up is a visual delivery technique in the form of three dimensions that falls under paper engineering, where paper is folded in such a way that it emerges or expands when a page is opened. This technique not only provides aesthetic value but also offers a more interactive reading experience for readers. Pop-up storybooks are designed to make the narrative within them come alive through the raised effects produced by folding techniques. Thus, readers not only enjoy the text but also gain a visual experience that supports their imagination of the story’s content. A well-designed pop-up book is determined by the effectiveness of the pop-up models used in clearly conveying the story’s message. The choice of folding models must align with the narrative so that the visual elements presented are not only aesthetically appealing but also communicative. This study aims to analyze the selection of pop-up models and to assess the extent to which these models successfully depict the story adapted from the Harry Potter film. The analysis results show that five types of pop-up models are used, namely magic box, V-folds, multiple layers, floating layers, and moving discs. Among these five, multiple layers are the most frequently used model, with a percentage of 35.3%. Meanwhile, effectiveness analysis indicates that 58.8% of the pop-up models employed successfully illustrate the story, both in terms of character visualization and storyline. In conclusion, the Harry Potter pop-up book demonstrates innovative and effective paper engineering techniques in storytelling. This proves that interactive media such as pop-up books can serve as a creative medium to enhance both the appeal and comprehension of readers toward a literary work or film adaptation.